DIMENSI SEJARAH MELAYU DALAM KUMPULAN SAJAK TERSEBAB HAKU MELAYU EDISI PENGGAL PERTAMA KARYA TAUFIK IKRAM JAMIL : KAJIAN STRUKTURALISME GENETIK - Ali, Ririn Fujiarti; Syafrial, Syafrial; Rumadi, Hadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study analyzes the dimension of Malaysian history in the poetry collection of Malaysian Haku causes using the Genetic Structuralism Study. The aspects analyzed include the intrinsic and extrinsic structures contained in the poem as well as the viewpoint of the author's world in a collection of Malaysian haku causal poems. This type of research is qualitative research with descriptive methods. The technique of collecting data is collecting tax data with Malaysian historical dimensions in a collection of poetry books entitled the causality of Malay haku using the technique of recording or transcribing data. Data transcription or type data with regard to obtained research data. The worldview of the author in the poetry collection of Taufik Ikram Jamil, caused by haku Melayu, is: social criticism of the social environment in Riau8, poetry, social criticism of the government of Indonesia and Malaysia3 poetry, author inspiration for historical events 2 poems, criticism on alienation of Malaysian 4 poemsKey Words: Dimensions of Malay History; Genetic Structuralism; Rhyme